Business Ethics: Law As A Determinant of Business Conduct - Di Lorenzo, Vincent (Journal of business ethics, 2007)
The Principles of Corporate Governance require that business conduct conform to the law. In recent years, news reports of business misconduct have cast doubt on a conclusion that conformity is the prevalent practice. This article explores the influence of law on business conduct by comparing the law’s requirements and purposes with actual business conduct in the market. Specifically, it explores whether certain legal regimes are more effective than others in inducing greater commitment to legal compliance by corporate actors. The conclusion drawn is that the prevalent legal regime – a vague common law or legislative mandate – is typically associated with corporate conduct that evades or ignores the law’s mandate or its underlying purpose.